Optimizing the Use of Matlab GUI Attributes in the Creation of Calculus Learning Media: An Effort to Measure Students' Innovative Attitudes - Sucipto, Lalu; Irpan, Samsul (IJECA (International Journal of Education and Curriculum Application), 2022)
Calculus learning requires a high level of visualization in instilling concepts optimally to students. Therefore, the purpose of this study is to look at students' innovative attitudes in developing matlab GUI-based learning media in solving calculus problems and see the influence of the ability to use matlab GUI attributes on the level of innovation of the students in developing learning media. In the early stages, the students developed media according to the given topic. In the second stage, the product was assessed in terms of its validity. The students' innovative attitudes were assessed by a team of experts using questionnaires with 5-point Likert scale. From the 16 media successfully developed, validation results were obtained with an average score of 3.83 which means "valid". Meanwhile, from the assessment of innovative attitudes, the students’ attitudes are in the category of "innovative" with an average score of 3.61. In addition, the results of the regression tests revealed that the innovative attitudes are influenced by the ability to use the matlab GUI attributes by 84.2%. The rest is influenced by other factors with similarities: . Lastly, the results of the assessment showed that the media belonged to the category of "very effective" (score 81.2%).